Representasi Gambar Peringatan Kesehatan Pada Kemasan Rokok (Analisis Semiotika Roland Barthes Berdasarkan Peraturan Menteri Kesehatan No 28 Tahun 2013) - M. Solikul Huda; Linda Astuti; Bayu Risdiyanto (UNIVED PRESS, Universitas Dehasen Bengkulu, 2017)
The Government Regulation No. 109 of 2012 on Security of materials containing additives in the form of tobacco products for health in value are no longer effective. In accordance with the provisions of the Government through the Minister of Health issued Regulation No. 28 of 2013 on the inclusion of health warning and health information on tobacco products in the form of images and writings. In the Minister of Health Regulation No. 28 of 2013, there are five images that must be applied to all Tobacco Products such as smoking pictures caused by oral cancer, smoking pictures kill you, smoking pictures caused by oral cancer, smoking pictures near the children are dangerous for them and smoking pictures caused by lung cancer and chronic bronchitis. The aim of this study is to find out the meaning of health warning images in cigarette packaging. It is the meaning of denotation, connotation and myth as revealed by Roland Barthes. The writer collected data from primary and secondary data and analyzed data by using Roland Barthes semiotics. This study uses a qualitative method.The results of this study can be concluded that the denotative meaning of health warning picture in government regulation No. 28 of 2013 is a form of warning in the form of a call about the consequences and appearance of the symptoms caused dangerous diseases, death, and distress for children caused by smoking. The connotative meaning built up is due to the neglect of the importance of warning and the call of dangerous diseases can lead to cancer, death, and harm to people around smokers. While the myths formed from the five images of health warning is a form of threat to smokers for the impact that occurred to immediately leave the habit and more concerned about his life and health.